Predictors of obstructive sleep apnoea‐hypopnea severity and oral appliance therapy efficacy by using lateral cephalometric analysis. (1st May 2016) - Sakamoto, Y.; Yanamoto, S.; Rokutanda, S.; Naruse, T.; Imayama, N.; Hashimoto, M.; Nakamura, A.; Yoshida, N.; Tanoue, N.; Ayuse, T.; Yoshimine, H.; Umeda, M.
Summary: Obstructive sleep apnoea‐hypopnea (OSAH) is a common disorder characterised by repetitive complete or partial closure of the upper airway during sleep, which results in sleep fragmentation and oxygen desaturation. There is growing interest in the use of oral appliances (OAs) to treat OSAH. The purpose of this study was to clarify the cephalometric factors that are associated with OSAH severity and that predict the outcome of OA therapy. Two hundred nine patients with OSAH were recruited and analysed retrospectively. They had a polysomnographically documented apnoea‐hypopnea index (AHI) of more than five respiratory events per hour. Lateral skull radiographs were used for cephalometric analysis. Only 67 of the 209 recruited patients underwent a second polysomnography (PSG) to evaluate the efficacy of OA therapy. In all recruited patients, the angle formed by the subspinal point (A) to the nasion (N) to the supramental point (B) (i.e. ANB angle) and the distance between the mandibular plane and hyoid bone (MP‐H) were predictive factors of OSAH severity. In only 67 patients underwent PSG with an OA, the mean rate of decrease in the AHI was 47·8 ± 29·1%. OA therapy effectively treated OSAH in some patients with a very severe form of OSAH. However, patients who had a high position of the hyoid bone had a poor response to OA therapy. This study suggested that cephalometric analysis is useful for predicting OSAH severity and OA therapy efficacy.